Esophageal varices presenting as lower GI bleed in an infant: a rare presentation - Choudaha, Anmol; Banzal, Rajeev Kumar; Mehrotra, Gunjan Kela; Sodha, Nandini (International Journal of Contemporary Pediatrics, 2020)
GI Bleeding is a common problem encountered in the emergency department and in the primary care settings. Lower GI Bleeding is relatively rare as compared to upper GI bleeding. Common causes of lower GI Bleeding are Polyp (32.5%), chronic nonspecific colitis (20.7%), lymphoid nodular hyperplasia (20%), Proctitis (18.2%), Solitary rectal ulcer (10%), Inflammatory bowel disease (6.5%).Among the various causes of lower GI Bleeding, esophageal varices is a rare cause. One such case presented to us with lower GI bleeding, on further evaluation was found to having esophageal varices due to portal hypertension. Child improved after conservative and definitive management.